2017
DOI: 10.9787/pbb.2017.5.2.78
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Efficiency of Selection Indices in Wheat (Triticum aestivum L.) under Drought Stress and Well-Irrigated Conditions

Abstract: This is an Open-Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License (http://creativecommons.org/licenses/by-nc/4.0) which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited. ABSTRACT Aggregate selection helps making selection decisions for improved profitability and permits to exploit information on correlated traits to improve accuracy. In the present study, the efficiency of trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…[10,15] noted higher genetic variability under drought than under irrigation. In addition, [16,18] reported that the variation decreased under drought stress because of the influence of the genotype by drought interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10,15] noted higher genetic variability under drought than under irrigation. In addition, [16,18] reported that the variation decreased under drought stress because of the influence of the genotype by drought interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Refs. [17,18] noted a greater reduction in heritability of most complex traits under drought than under irrigation conditions, which may be due to the decrease in genetic variation and the influence of the genotype by drought interaction. Ref.…”
Section: Introductionmentioning
confidence: 97%
“…All landraces under study did not differ statistically significantly from each other, nor compared to the improved line, regarding their seed yield (kg ha −1 ). This fact is probably due to the unfavorable field conditions, which led to the production of low seed yield and did not allow landraces’ potential to be unfolded in our study [ 78 , 79 , 80 ]. In particular, the seed yield of the VG2 landrace from Atsiki of Lemnos was low (0.56 t ha −1 on average).…”
Section: Discussionmentioning
confidence: 99%
“…The breeder may use such selected families in breeding programs aimed at increasing wheat grain yield. Overall, grain yield estimates were low, indicating that individual plant selection is inefficient for wheat improvement whereas aggregate trait selection results in relatively large genetic gain for grain yield (Ghaed-Rahimi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%